Commutators of Square Functions Related to Fractional Differentiation for Second-Order Elliptic Operators. (2nd December 2018) - Wu, Xiongtao; Tao, Wenyu; Chen, Yanping; Zhu, Kai
Abstract : LetL = - d i v ( A ∇ ) be a second-order divergence form elliptic operator, whereA is an accretiven × n matrix with bounded measurable complex coefficients inR n . In this paper, we mainly establish theL p boundedness for the commutators generated byb ∈ I α ( B M O ) and the square function related to fractional differentiation for second-order elliptic operators.